Engineering Purse Line Hauler Machine For Hydraulic Axle Capstan On Mini Purse Seine Boat - Soepardi, Sugiono; Istrianto, Kadi; Fanani, M. Zainal; Samu, Markus Samu; Suharyanto, Suharyanto; Perangin-angin, Robet (PELAGICUS, 2023)
Purse seine or purse seine is one of the dominant fishing tools for catching pelagic (surface) fish which operates by circling schools (schooling) of fish. In the process of circling a school of fish, the bottom must be crimped immediately and quickly using a crimping rope or what is usually called a "drawstring" so that the fish remain in the circle and do not escape. This research was conducted from August to October 2019 on the north coast of Pekalongan, Java Sea. The application of hydraulically powered capstan axle crimp rope pulling machines on small scale vessels is expected to increase effectiveness, operational safety and efficiency of time and energy. Especially for purse seine ships <30GT and can increase catches which in turn can increase fishermen's income. Based on the test results, it was found that the driving diesel RPM without a pulling load = 1303 / 1530 RPM; Maximum RPM of the winding capstan spool when without a pulling load = 45 / 51.5 RPM; Maximum speed of winding capstan spools without tension load = 40.5 / 58.5 meters/minute; RPM of the driving diesel when pulling the purse seine line = 1500 RPM; Maximum RPM of the capstan winder spool when pulling the purse seine line at an average load = 43.2 RPM; Maximum RPM of the capstan winder spool when pulling the heaviest load (maximum) purse seine crimp rope = 40.1 RPM; Maximum pulling speed of the towing machine at the average load of pulling the purse seine crimp rope = 40.07 meters/minute; Maximum pulling speed of the towing machine when the heaviest load is pulling the purse seine crimp rope = 37.2 meters/minute; Load towing capability = detected ± 1000kg.